2022
DOI: 10.1039/d1cy02271g
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of Asp206 stabilizing residues on the catalytic mechanism of the Ideonella sakaiensis PETase

Abstract: Plastic accumulation is one of the main environmental issues of our time. In 2016, two enzymes capable of degrading Polyethylene terepthtalate (PET) , one of the most common plastic polymers,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 68 publications
(111 reference statements)
0
13
0
Order By: Relevance
“…For PETases to be applied industrially to aid in the depolymerization and recycling of PET, they typically need to be engineered to increase their kinetic and thermal stability, as well as their catalytic efficiency. These approaches have ranged from random mutagenesis to computational design, machine learning, and rational design. Most mutated residues are targeted to modify the substrate binding site, the wobbling tryptophan residue and those in the vicinity of the disulfide bond in the active site. ,,, As a result, numerous protein engineering efforts have succeeded in developing more stable and active variants, including DuraPETase, ThermoPETase, HotPETase, and FAST-PETase. Recently, Lu et al demonstrated that FAST-PETase could almost completely degrade untreated, postconsumer PET samples within 1 week and recover the monomers .…”
mentioning
confidence: 99%
“…For PETases to be applied industrially to aid in the depolymerization and recycling of PET, they typically need to be engineered to increase their kinetic and thermal stability, as well as their catalytic efficiency. These approaches have ranged from random mutagenesis to computational design, machine learning, and rational design. Most mutated residues are targeted to modify the substrate binding site, the wobbling tryptophan residue and those in the vicinity of the disulfide bond in the active site. ,,, As a result, numerous protein engineering efforts have succeeded in developing more stable and active variants, including DuraPETase, ThermoPETase, HotPETase, and FAST-PETase. Recently, Lu et al demonstrated that FAST-PETase could almost completely degrade untreated, postconsumer PET samples within 1 week and recover the monomers .…”
mentioning
confidence: 99%
“…The reaction mechanism matches that from previous works, suggesting a two-step acylation with the tetrahedral intermediate state a shallow minimum on the free energy surface. 15,17,[22][23][24][25]30,32 Firstly, the catalytic histidine abstracts a proton from the catalytic serine, resulting in TS1. Then, the serine attacks the ester carbon, yielding the tetrahedral intermediate with its oxyanion stabilised by the oxyanion hole.…”
Section: Pet Ring Orientation Change Correlates With Acylationmentioning
confidence: 99%
“…1). [15][16][17][23][24][25][26] Figure 1: Mechanism of PET-degradation as proposed by Boneta et al 15 The mechanism can be divided into two steps: First, the acylation of the Michaelis complex (MC) yielding the acyl-enzyme intermediate (AE) and second, the hydrolysis yielding the product complex (PC), both incorporating a tetrahedral intermediate (TI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that there have been multiple elegant computational studies that have helped reveal the mechanisms of PET-degrading enzymes, more global conformational changes involved in catalysis, , and contributed to associated engineering effort. However, corresponding studies of the conformational dynamics of this catalytically important tryptophan remain limited. Therefore, to explore the importance of the S214/I218 substitution for PET hydrolytic activity, doubly substituted variants of the strictly conserved histidine and phenylalanine residues in several PET hydrolases, including the mesophilic Bur PL from a Burkholderiales bacterium (H344/F348), and the thermophilic Tf Cut from Thermobifida fusca (H224/F228) and LCC (H218/F222), were generated based on the S214/I218 residues unique to Is PETase.…”
Section: Introductionmentioning
confidence: 99%